Spatiotemporal dynamics of homologous recombination repair at single collapsed replication forks - Donna R. Whelan (Nature Portfolio, 2018)
How factors involved in homologous recombination interact and function is a matter of interest. Here the authors use super-resolution imaging to describe the spatiotemporal dynamics of proteins associated with homologous recombination DNA repair in response to replication stress.